2005
DOI: 10.2320/matertrans.46.3008
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Wetting of Liquid Metals on Iron Substrate with Oxidized Surface in Reduced Atmosphere

Abstract: The authors found that a liquid Cu droplet wetted and spread very widely on a solid substrate of Fe in a reduced atmosphere after the surface oxidation of the substrate. The mechanism of the unusual wetting behavior was investigated by using surface-oxidized Fe substrate with liquid Cu, Ag, Sn, and In. It was found that under a reduced atmosphere condition, fine pores were formed at the surface of the substrate which had been oxidized, and that the pores were connected to each other continuously over the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Intermetallic compounds do not exist in a binary Bi-Cu system, and their mutual solubility is low at low temperature 7) . The contact angle between solid Cu and liquid Bi is lower than 90 above 600 K; i.e., liquid Bi wets solid Cu at such a temperature 3,8) . Therefore, unusual wetting involving capillary action in a wetting system can occur without any reaction of the two elements, such as compound formation in a Bi-Cu binary system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermetallic compounds do not exist in a binary Bi-Cu system, and their mutual solubility is low at low temperature 7) . The contact angle between solid Cu and liquid Bi is lower than 90 above 600 K; i.e., liquid Bi wets solid Cu at such a temperature 3,8) . Therefore, unusual wetting involving capillary action in a wetting system can occur without any reaction of the two elements, such as compound formation in a Bi-Cu binary system.…”
Section: Methodsmentioning
confidence: 99%
“…Originally, Tanaka and coworkers [1][2][3] found that unusual wetting occurs on the surface ne porous structure formed by treating atmospheric oxidation-reduction for metal surface, and reported that unusual wetting have a potential to achieve a joining with minimum overlay formation in brazing and soldering. Recently, the authors [4][5][6] have discovered a new way to create the structure surface ne crevice structure for unusual wetting by means of laser-irradiation to the surface of copper (Cu) and iron.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study, 1) the authors have found that the unusual wetting behaviors of liquid metals on iron substrates were observed when the metal droplets were attached to the substrates prepared by oxidation-reduction processes, and have subsequently reported a mechanism to account for this unusual wetting phenomenon. In particular, a Cu droplet wetted and spread widely on an iron substrate, to an extent that the substrate surface was coated entirely by the liquid metal.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study 1) found that unusual wetting behaviors of liquid metals (Cu, Ag, Sn, and In) on iron substrates occurred when the metal droplets were attached to the substrates prepared by oxidationreduction processes, and we have subsequently reported on the mechanism of this unusual wetting phenomenon. The aim of this paper is to investigate wetting behaviors of liquid indium and bismuth on flat iron substrates, and to relate these behaviors to unusual wetting phenomenon.…”
Section: Introductionmentioning
confidence: 99%